AN ORIGINAL OR EXACT RESEARCH ARTICLE APPROBATION PROCEDURE - YONK, DR . FANDY (International Journal of Multidisciplinary Research and Studies, 2019)
This essay establishes CIIT, the foremost hybrid research paper recommender system along with a powerful substitute to presently used academic search engines. CIIT develops the look of the typically implemented keyword-based search through uniting it by citation analysis, author analysis, implicit ratings, source analysis, explicit ratings and also, pioneering and yet idle methods similar to the ‘Distance Similarity Index’ (DSI) as well as the ‘In-text Impact Factor’ (ItIF). Rather than searching just keywords, a user may give whole documents, as well as reference lists as input as well as make implicit and explicit ratings to develop recommendations. With a quotation, author along with source analysis, similar and associated documents are effortlessly determinable. Every one of these methods is managed with an accessible GUI.